2004
DOI: 10.1002/jtra.10054
|View full text |Cite
|
Sign up to set email alerts
|

Compound load of copper and iron in the livers of pretreatment patients with Wilson's disease

Abstract: Ceruloplasmin is a major ferroxidase in sera, and people with hypoceruloplasminemia might have iron load complications. We used histochemical and X-ray microanalysis techniques on pretreatment liver specimens from five patients with WilsonÕs disease. Serum levels of ceruloplasmin and ferritin were determined before chelation therapy. All the patients showed hypoceruloplasminemia ranging from 15 to 160 mg/L. Histochemical copper was positively stained in four of the five patients. Copper deposits were clearly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
0
9
0
2
Order By: Relevance
“…Regardless of the initial symptoms, their livers were affected by copper toxicosis, resulting in either chronic hepatitis or cirrhosis. The compound overload of copper and iron in the patients was reported in detail elsewhere 15–17 . Histochemical tests for cuprothioneins should be positive in this disease, but were negative in one patient because of a sampling error.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Regardless of the initial symptoms, their livers were affected by copper toxicosis, resulting in either chronic hepatitis or cirrhosis. The compound overload of copper and iron in the patients was reported in detail elsewhere 15–17 . Histochemical tests for cuprothioneins should be positive in this disease, but were negative in one patient because of a sampling error.…”
Section: Introductionmentioning
confidence: 51%
“…Because ceruloplasmin is a major ferroxidase, iron transport is also affected in the liver and other iron storage organs of hypoceruloplasminemic patients. Their hepatocellular lysosomes might thus be shared by cuprothioneins and iron complex 15–17 . The histochemistry for iron and copper is not so sensitive that X‐ray microanalysis is recommended for the liver specimens obtained from patients with Wilson disease (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, the iron load in WD was not discussed in the study. In previous studies, we reported the co-existence of copper and iron in hepatocyte lysosomes of WD patients without HH traits [15,17]. It must be emphasized that the methods applied here have at least 2 advantages over the traditional methods [18].…”
Section: S Motonishi Et Al 412mentioning
confidence: 97%
“…In a previous study, we reported the compound load of copper and iron in the livers of pretreatment patients with WD [17]. Almost the same distribution of copper and sulfur in the electron dense bodies suggested that copper formed a sulfhydryl-rich complex, metallothionein.…”
mentioning
confidence: 89%
See 1 more Smart Citation